Modifying the sensory profile of green honeybush (Cyclopia maculata) herbal tea through steam treatment. (1st September 2017) - Alexander, Lara; de Beer, Dalene; Muller, Magdalena; van der Rijst, Marieta; Joubert, Elizabeth
Abstract: Green honeybush ( Cyclopia spp.), superior to the traditional "fermented" product in bioactive phenolic content, is not well accepted by consumers due to its predominant vegetal aroma. Steam treatment of fresh, shredded plant material (0, 30, 60, 90 and 120 s) and dried, shredded plant material (0, 1, 2, 3 and 4 min) of Cyclopia maculata was investigated to improve the aroma of the infusion, but without compromising green colour and phenolic content of the product. Steam treatment increased and decreased fruity and vegetal aroma attribute intensities, respectively. The dried plant material was less susceptible than the fresh plant material to the impact of steam. The fresh and dried plant material should be steam-treated for at least 60 s and 2 min, respectively. Steam treatment had little impact on leaf colour, although the total chlorophyll content was decreased. The individual polyphenol content of the plant material also remained largely unaffected, with reductions in the content of some compounds only when the fresh plant material was steam-treated for 30 s (mangiferin, isomangiferin, 3-β-d -glucopyranosyliriflophenone and hesperidin) and dried plant material steam-treated for 4 min (eriodictyol- O -glucopyranoside). Except for hesperidin, longer steam treatment of the fresh plant material did not affect its individual phenolic content. Highlights: Green honeybush has a predominant vegetal aroma. Steam treatment of the plant material improved its aroma. Steam treatment increased fruity and decreased vegetative aroma intensities. Steam treatment did not compromise green leaf colour or phenolic content.